Feasibility Analysis of Spice Coffee Processing Business in Home Industries in Tabahawa Village, Ternate City - Fatmawati Fatmawati; Munawir Muhammad; Rusli Fokaya (Agrikan: Jurnal Agribisnis Perikanan, 2020)
Most of the use of coffee today is processed into drinks, with various types, brands and one of them is spice coffee which has been produced in the households of Ternate City, Tabahawa Village. Spice coffee is coffee that mixed with spice powder, namely robusta coffee, cinnamon, nutmeg, cloves, ginger and sugar. Spice coffee has a warm spicy taste and this coffee has been marketed in stores or supermarkets in Ternate City. Various kinds of beverage products can be made using the basic ingredients of coffee, this is because coffee has a distinctive taste and a refreshing effect. Spices also provide a specific aroma to suit one's taste with a distinctive spice refreshing and warming effect. By combining coffee and spices which have almost the same active compound, it is possible to create mixed flavors that consumers can enjoy. Seeing this potential, it is necessary to conduct research on the Analysis of Spice Coffee Processing Business in the Household Industries of Tabahawa Village, Ternate City. The purpose of this research was to analyze the feasibility of the spice coffee processing business in the Household Industry of Tabahawa Village, Ternate City. The analysis method used in this research are NPV analysis, B / C Ratio, IRR and Payback period. Through the results of the research that the process of making spice coffee includes: All raw materials are ground separately into powder, then the powder is mixed so that it becomes one according to the comparison and to answer the second problem through a financial feasibility analysis that the spice coffee processing business shows that, the NPV value is obtained amounting to Rp.41,437,982, the IRR value obtained is 202.5%, the Cost Ratio value is 0.06%, the Gross B / C Ratio value is Rp.53,717,982, while the calculation of the criteria for the return on investment (playback period) is obtained for 1 year. Investment costs can be covered through profits after the business has been running for 2 years so that the home coffee spice industry is feasible to develop.